An Indicator for Risk of Phosphorus Loss from Sandy Soils - Vimala D. Nair; Willie G. Harris; Debolina Chakraborty (EDIS, 2010)
SL333, a 3-page illustrated fact sheet by Vimala D. Nair, Willie G. Harris, and Debolina Chakraborty, describes a practical means of determining when a soil has reached a level of P loading that constitutes an environmental risk. Includes references. Published by the UF Department of Soil and Water Sciences, October 2010.